2001
DOI: 10.1016/s0893-133x(01)00256-1
|View full text |Cite
|
Sign up to set email alerts
|

The Selective mGlu5 Receptor Agonist CHPG Inhibits Quinpirole-Induced Turning in 6-Hydroxydopamine-Lesioned Rats and Modulates the Binding Characteristics of Dopamine D2 Receptors in the Rat Striatum Interactions with Adenosine A2a Receptors

Abstract: In 6-hydroxydopamine-lesioned rats, the selective mGlu 5 receptor agonist (1)(2)(3)(4)(5)(6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 41 publications
4
117
0
Order By: Relevance
“…Recent evidence have shown that agonists acting at A 2A and group I mGlu receptors were able to reduce either separately or in costimulation the high-affinity state of the DA D2 receptor binding sites (Ferré et al, 1999). A functional antagonistic relationship of D 2 with A 2A and mGlu 5 receptors is further supported by a recent study showing that the mGlu5 receptor agonist, CHPG, inhibit the D 2 -induced turning behavior in unilateral 6-OHDA-lesioned animals, an effect greatly potentiated by a joint administration with the A 2A receptor agonist CGS 21680 (Popoli et al, 2001). It might then be suggested that the complete recovery of DA-induced deficits observed in the present study after a concomitant blockade of mGlu 5 and A 2A receptors result from a normalization of the overactive striatopallidal GABA pathway.…”
Section: Functional Interaction Between a 2a And Mglu 5 Receptorsmentioning
confidence: 79%
“…Recent evidence have shown that agonists acting at A 2A and group I mGlu receptors were able to reduce either separately or in costimulation the high-affinity state of the DA D2 receptor binding sites (Ferré et al, 1999). A functional antagonistic relationship of D 2 with A 2A and mGlu 5 receptors is further supported by a recent study showing that the mGlu5 receptor agonist, CHPG, inhibit the D 2 -induced turning behavior in unilateral 6-OHDA-lesioned animals, an effect greatly potentiated by a joint administration with the A 2A receptor agonist CGS 21680 (Popoli et al, 2001). It might then be suggested that the complete recovery of DA-induced deficits observed in the present study after a concomitant blockade of mGlu 5 and A 2A receptors result from a normalization of the overactive striatopallidal GABA pathway.…”
Section: Functional Interaction Between a 2a And Mglu 5 Receptorsmentioning
confidence: 79%
“…Such a mechanism was recently proposed for the induction of LTD in the cerebral cortex (Otani et al, 1999). Another possibility would be that mGluR5 and dopamine receptors functionally interact via direct protein-protein interactions, a phenomenon that has been characterized for other G-protein-coupled receptors in the CNS including dopamine and adenosine receptors with group I mGluRs (Ciruela et al, 2001;Popoli et al, 2001;Ferre et al, 2002). The fact that mGluR5 and dopamine receptors display a similar pattern of subsynaptic distribution relative to dopaminergic synapses (Yung et al, 1995) supports the possibility of functional interactions between these receptors.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, intrastriatal injection of nonselective or group I mGlu receptor agonists induced delayed contralateral turning behavior, which is possibly mediated by the potentiation of action of adenosine A 2A receptors in striatopallidal neurons followed by the disinhibition of subthalamic nucleus neurons, with the consequent increase in output of dopaminergic nigrostriatal neurons (28). In 6-hydroxydopamine-lesioned rats, the intracerebroventricular injection of an mGlu5 agonist counteracted the contralateral turning behavior elicited by a dopamine D2 agonist, which could be explained by the potentiation of reciprocal interaction between adenosine A 2A and dopamine D2 receptors (30). Recently, Chiamulera et al (11) reported that mice lacking the mGlu5 receptor do not self-administer cocaine and show no increased locomotor activity after cocaine treatment, despite the increase in dopamine release in nucleus accumbens.…”
Section: Discussionmentioning
confidence: 99%